2011
DOI: 10.1111/j.1532-5415.2011.03424.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Group Variations in Service Use in a National Sample of Medicare Home Health Care Patients with Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus is known to affect adults in racial and ethnic minority groups disproportionately. When diabetes mellitus–related symptoms lead to the need for skilled care in the community-dwelling Medicare population, physicians can order the Medicare home health care (HHC) benefit, and Medicare-certified home health agencies can deliver it. Little is known about the extent to which racial and ethnic disparities exist in types and patterns of HHC services delivered to Medicare beneficiaries with dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…In general, it is logical to expect higher education to be associated with lower prevalence of diabetes mellitus because individuals who are educated are more likely to understand the risk factors for diabetes mellitus and apply this knowledge in controlling behavior towards risk factors reduction, namely, alcohol, smoking, and physical inactivity. Lower education level has been associated with increased risk of diabetes mellitus and other chronic diseases [29][30][31][32], and our results clearly support these previous data [33][34][35][36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 82%
“…In general, it is logical to expect higher education to be associated with lower prevalence of diabetes mellitus because individuals who are educated are more likely to understand the risk factors for diabetes mellitus and apply this knowledge in controlling behavior towards risk factors reduction, namely, alcohol, smoking, and physical inactivity. Lower education level has been associated with increased risk of diabetes mellitus and other chronic diseases [29][30][31][32], and our results clearly support these previous data [33][34][35][36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 82%
“…In the context of Medicare HHC, because hospitalization is considered an indicator of potentially poorer quality of care, one explanation for this finding is that Blacks may receive inferior quality of HHC. A recent national study of HHC patients with a primary diagnosis of type 2 diabetes mellitus found that Blacks received less skilled care from nurses and from rehabilitation therapists during their HHC episodes than did their White counterparts (Yeboah-Korang, Kleppinger, & Fortinsky, 2011). An equally plausible alternative explanation is that Black Medicare HHC patients are more likely than their White counterparts to lack access to primary care, and to have fewer resources to manage their chronic conditions despite receiving HHC, both of which may lead to greater risk for hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…A patient’s physical status influenced visit intensity. Other researchers established that patients with open wounds receive more nurse visits per week compared to those with other needs (Yeboah-Korang, Kleppinger, & Fortinsky, 2011). Few participants mentioned assessing the patient’s cognitive ability to evaluate the need for additional visits and reinforcement.…”
Section: Discussionmentioning
confidence: 99%